Targeting of ανβ3-integrins expressed on tumor tissue and neovasculature using fluorescent small molecules and nanoparticles. (July 2010) - Akers, Walter J; Zhang, Zongren; Berezin, Mikhail; Ye, Yunpeng; Agee, Anthony; Guo, Kevin; Fuhrhop, Ralph W; Wickline, Samuel A; Lanza, Gregory M; Achilefu, Samuel
Aim: Receptor-specific small molecules and nanoparticles are widely used in molecular imaging of tumors. Although some studies have described the relative strengths and weaknesses of the two approaches, reports of a direct comparison and analysis of the two strategies are lacking. Herein, we compared the tumor-targeting characteristics of a small near-infrared fluorescent compound (cypate–peptide conjugate) and relatively large perfluorocarbon-based nanoparticles (250 nm diameter) for imaging αν β3 -integrin receptor expression in tumors.Materials & methods: Near-infrared fluorescent small molecules and nanoparticles were administered to living mice bearing subcutaneous or intradermal syngeneic tumors and imaged with whole-body and high-resolution optical imaging systems.Results: The nanoparticles, designed for vascular constraint, remained within the tumor vasculature while the small integrin-avid ligands diffused into the tissue to target integrin expression on tumor and endothelial cells. Targeted small-molecule and nanoparticle contrast agents preferentially accumulated in tumor tissue with tumor-to-muscle ratios of 8 and 7, respectively, compared with 3 for nontargeted nanoparticles.Conclusion: Fluorescent small molecular probes demonstrate greater overall early tumor contrast and rapid visualization of tumors, but the vascular-constrained nanoparticles are more selective for detecting cancer-induced angiogenesis. A combination of both imaging agents provides a strategy to image and quantify integrin expression in tumor tissue and tumor-induced neovascular systems.